1988
DOI: 10.1111/j.1472-8206.1988.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noradrenaline on the Isolated Human Bronchus. Comparison With the Isolated Guinea Pig Trachea

Abstract: The pharmacodynamic activity of noradrenaline was evaluated comparatively in vitro on isolated human bronchi and on guinea pig tracheal spirals. Noradrenaline exerted a contractile effect on both preparations under resting tone and in the presence of propranolol 10(-6) M; maximal noradrenaline-induced contraction was 15-20% of maximal acetylcholine (ACh)-induced contraction. Without propranolol, the contractile effect of noradrenaline was negligible when the preparations were under resting tone and absent when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…In contrast, (−)‐adrenaline and (−)‐noradrenaline caused contraction in rat isolated tracheal preparations in the presence or absence of (±)‐propranolol. These results are in agreement with previous findings indicating that in the absence of β‐adrenoceptor blocking agents, noradrenaline exerts a strong relaxant effect with negligible contractile activity in guinea‐pig trachea (Naline et al ., 1988). Furthermore, it has been demonstrated that rat trachea and bronchi have little or no intrinsic tone (Burns & Doe, 1978).…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, (−)‐adrenaline and (−)‐noradrenaline caused contraction in rat isolated tracheal preparations in the presence or absence of (±)‐propranolol. These results are in agreement with previous findings indicating that in the absence of β‐adrenoceptor blocking agents, noradrenaline exerts a strong relaxant effect with negligible contractile activity in guinea‐pig trachea (Naline et al ., 1988). Furthermore, it has been demonstrated that rat trachea and bronchi have little or no intrinsic tone (Burns & Doe, 1978).…”
Section: Discussionsupporting
confidence: 94%